Laparoscopic versus open pancreaticoduodenectomy for pancreatic and periampullary tumor: A meta-analysis of randomized controlled trials and non-randomized comparative studies - Yan, Yong; Hua, Yinggang; Chang, Cheng; Zhu, Xuanjin; Sha, Yanhua; Wang, Bailin (Frontiers in Oncology, 2023)
Objective This meta-analysis compares the perioperative outcomes of laparoscopic pancreaticoduodenectomy (LPD) to those of open pancreaticoduodenectomy (OPD) for pancreatic and periampullary tumors. Background LPD has been increasingly applied in the treatment of pancreatic and periampullary tumors. However, the perioperative outcomes of LPD versus OPD are still controversial. Methods PubMed, Web of Science, EMBASE, and the Cochrane Library were searched to identify randomized controlled trials (RCTs) and non-randomized comparative trials (NRCTs) comparing LPD versus OPD for pancreatic and periampullary tumors. The main outcomes were mortality, morbidity, serious complications, and hospital stay. The secondary outcomes were operative time, blood loss, transfusion, postoperative pancreatic fistula (POPF), postpancreatectomy hemorrhage (PPH), bile leak (BL), delayed gastric emptying (DGE), lymph nodes harvested, R0 resection, reoperation, and readmission. RCTs were evaluated by the Cochrane risk-of-bias tool. NRCTs were assessed using a modified tool from the Methodological Index for Non-randomized Studies. Data were pooled as odds ratio (OR) or mean difference (MD). This study was registered at PROSPERO (CRD42022338832). Results Four RCTs and 35 NRCTs concerning a total of 40,230 patients (4,262 LPD and 35,968 OPD) were included. Meta-analyses showed no significant differences in mortality (OR 0.91, p = 0.35), serious complications (OR 0.97, p = 0.74), POPF (OR 0.93, p = 0.29), PPH (OR 1.10, p = 0.42), BL (OR 1.28, p = 0.22), harvested lymph nodes (MD 0.66, p = 0.09), reoperation (OR 1.10, p = 0.41), and readmission (OR 0.95, p = 0.46) between LPD and OPD. Operative time was significantly longer for LPD (MD 85.59 min, p < 0.00001), whereas overall morbidity (OR 0.80, p < 0.00001), hospital stay (MD −2.32 days, p < 0.00001), blood loss (MD −173.84 ml, p < 0.00001), transfusion (OR 0.62, p = 0.0002), and DGE (OR 0.78, p = 0.002) were reduced for LPD. The R0 rate was higher for LPD (OR 1.25, p = 0.001). Conclusions LPD is associated with non-inferior short-term surgical outcomes and oncologic adequacy compared to OPD when performed by experienced surgeons at large centers. LPD may result in reduced overall morbidity, blood loss, transfusion, and DGE, but longer operative time. Further RCTs should address the potential advantages of LPD over OPD. Systematic review registration PROSPERO, identifier CRD42022338832.